Politics and government - Wood, Richard (Wayland London, 1995)
The book Politics and Government by Richard Wood is part of the LEGACIES series, which examines how modern political systems and governmental structures have been influenced by ancient civilizations. This title explores the enduring impact of historical political practices on contemporary governance.